PrEP-001 prophylactic effect against rhinovirus and influenza virus - RESULTS of 2 randomized trials - Malcolm, Bruce Albert; Aerts, Caroline Anne; Dubois, Kristof Johan; Geurts, Frederik Joris; Marien, Kris; Rusch, Sarah; Van Dijck, Alex Henri; Verloes, Rene; Vingerhoets, Johan (Antiviral research, 2018)
PrEP-001 Nasal Powder, a proprietary formulation of polyriboinosinic and polyribocytidylic acid effectively elicits a cellular innate immune response in nasal epithelium. The aim of these 2 studies was to investigate the safety and efficacy of PrEP-001 prophylaxis against rhinovirus (HRV-A16) and influenza-A (H3N2-IAV). Healthy subjects randomly received 2 doses of PrEP-001 or placebo, 48 and 24 h pre-challenge with 10 TCID50 of HRV-A16 (Study 1) or H3N2-IAV (Study 2). In Study 1, PrEP-001 reduced median total symptom score from 38.5 to 4.5 (p = 0.004), median symptom duration from 6.0 to 1.7 days and median mucus production from 15 g to 3 g. The percentage of subjects classified as ill was reduced 3-fold (placebo 73%, PrEP-001 23%, p = 0.002). In Study 2, PrEP-001 reduced median total symptom score from 8.0 to 4.1 (p = 0.021), median symptom duration from 4.6 to 3.7 days and median mucus production from 3.6 g to 1.5 g. The percentage of subjects classified as ill was reduced 2-fold (placebo 48%, PrEP-001 24%, p = 0.064). PrEP-001 reduced peak viral shedding in both studies, as assessed by qRT-PCR of nasal lavage. Seroconversion rates were comparable between placebo and PrEP-001 (Study 1: 77% [both arms]; Study 2: placebo 73%, PrEP-001 80%). PrEP-001 was well-tolerated, with no clinically significant adverse events. PrEP-001 reduced the number of individuals with clinical illness and attenuated severity and duration of HRV-A16 and H3N2-IAV infections without compromising seroconversion, and was well-tolerated. This supports further evaluation of PrEP-001 as a potential pan-viral prophylaxis for upper respiratory tract infections. Study 1, HRV-A16 study: EudraCT Number 2012-005579-14 (study conducted before ClinicalTrials.gov registration required). Study 2, H3N2-IAV study: EudraCT Number 2015-002895-26 and ClinicalTrials.gov: NCT03220048.